Extracorporeal potassium binding for the management of hyperkalemia in an anephric model of crush injury. Issue 4 (April 2019) - Hoareau, Guillaume L.; Beyer, Carl A.; Wilson, Christopher; Kashtan, Harris; Wishy, Andrew; Grayson, J. Kevin; Walker, Lauren; Ross, James D.; Stewart, Ian J.
Abstract : BACKGROUND: Potassium-binding polymers have shown promising results in an anephric porcine hyperkalemia model. The benefits of the polymer in a clinically relevant injury model remain unknown. We hypothesized that potassium-binding cartridges would control serum potassium concentration in a porcine hemorrhagic shock model with supraceliac aortic occlusion and a limb crush injury. METHODS: Ten Yorkshire-cross swine were anesthetized and instrumented. Pigs underwent splenectomy and bilateral nephrectomy. Hemorrhagic shock was induced for 30 minutes while a leg compression device was applied. Pigs underwent supraceliac aortic occlusion for 60 minutes and were resuscitated with shed blood. The leg compression device was removed 20 minutes after balloon deflation. After 20 minutes of reperfusion, animals were randomized to extracorporeal circulation with (treatment) or without (control) the potassium binding cartridges. In both groups, blood was circulated through a hemodialyzer with a peristaltic pump. In the treatment group, the ultrafiltrate was diverted from the hemodialyzer through cartridges containing the polymer and returned to the extracorporeal circuit. Animals were resuscitated with 0.9% saline boluses and a norepinephrine infusion. The change in serum potassium concentration (ΔK) was calculated as serum [K + ]T390 − serum [K + ]T0 . RESULTS: There was a significant difference in serum potassium concentration between groups ( p < 0.001). ΔK was significantly higher in the control than the treatment group (3.75 [3.27–4.42] and 1.15 [0.62–1.59] mmol/L, respectively; p = 0.03). There were no differences in mean arterial pressure ( p = 0.14), isotonic crystalloids requirement ( p = 0.51), or norepinephrine dose ( p = 0.83) between groups. Serum lactate concentration was significantly higher in the control group ( p < 0.001). At the end of the experiment, the [K + ] was reduced by 25% (24.9%–27.8%) across the cartridges. CONCLUSION: The cartridges controlled serum potassium concentrations without dialysate and retained potassium binding capabilities over 4 hours. There were no deleterious effects on hemodynamic parameters. Those cartridges might be beneficial adjuncts for hyperkalemia management in austere environments. LEVEL OF EVIDENCE: Translational science study, level I. Abstract : Supplemental digital content is available in the text.